PENDEKATAN PEMBELAJARAN BERBASIS MASALAH UNTUK M.ENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD DALAM PEMBELAJARAN PKN - Fathurrohman Fathurrohman (MAJALAH ILMIAH PEMBELAJARAN, 2008)
PKn learning at elementary school associated as a bored lesson, becausethe student did not have free thinking and free assumptions about thelesson it self. This problem causes student interest in PKn at elemenlwJ'school ;s very low. One strategy that we can do is repair learning pallernthat can enhance critical thinking. ability with problem based learningapproach. Problem based learning is a kind of approach oriented lo skillof solving problems and to trained student critical thinking, rational , ndresponsible, The elementary student need to trained earlier to make adecision compatible with their understanding.